Combining acid-based deep eutectic solvents and microwave irradiation for improved chestnut shell waste valorization. Issue 24 (26th November 2021) - González-Rivera, José; Mero, Angelica; Husanu, Elena; Mezzetta, Andrea; Ferrari, Carlo; D'Andrea, Felicia; Bramanti, Emilia; Pomelli, Christian S.; Guazzelli, Lorenzo
Abstract : Key features of the deep eutectic solvent-microwave assisted simultaneous extraction of polyphenols and delignification pretreatment of chestnut shell waste are presented. Abstract : A microwave (MW)/deep eutectic solvent (DES)-assisted (MWDA) extraction process for obtaining value-added compounds from chestnut shell waste (CSW) is presented. DESs were used as green solvents featuring both high biomass dissolution ability and good response to MW irradiation. A survey of different acid-based DESs led to the identification of Choline Chloride (ChCl)–oxalic acid as the system most sensitive to experimental design variations, especially when considering the total phenolic content (TPC) and the total mass amount recovered (yield wt%). Hence, the MW absorption properties of ChCl–oxalic acid dihydrate and ChCl–oxalic acid DESs, as single components and in mixture with water, were assessed by the experimental determination of their MW heating response. Moreover, the extraction efficiency for the best MW responding system, ChCl–oxalic acid dihydrate, was evaluated at different MW-irradiation times and extraction temperatures. The isolated polyphenols from CSW were further characterized by HPLC-DAD analysis. Gallic acid, ellagic acid, catechin hydrate and procyanidin B2 were identified and quantified, with their relative ratios varying as a function of the MWDA extraction conditions. Lignin, hemicellulose and cellulose compositions of the solid residues of CSW after the MWDA extraction were assessed using a cross validation model obtained by partial least squares regression (PLS) of their FTIR spectra. The chemometrics results, corroborated by SEM analyses, highlighted the ability of the oxalic acid-based DES to simultaneously remove lignin during polyphenol extraction. Overall, the MWDA extraction process presented here enables the fast, cheap and tunable processing of food waste yielding a high amount of valuable bioactive compounds.